2017
DOI: 10.25011/cim.v40i3.28394
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparisons of bisphosphonates and teriparatide in osteoporosis: a meta-analysis

Abstract: Head-to-head comparisons of bisphosphonates and teriparatide in osteoporosis: a meta-analysis Abstract Purpose: This meta-analysis aimed to compare the efficacy and safety of teriparatide vs. bisphosphonates in the management of osteoporosis.Methods: A total of 1,967 patients from eight randomized controlled trials were analyzed; outcomes included bone mineral density (BMD) of the femoral neck, total hip and lumbar spine, vertebral and nonvertebral fractures and any adverse event. A subgroup analysis of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
3
16
0
5
Order By: Relevance
“…The agent teriparatide may be an alternative treatment for steroid-induced bone thinning. 75,76 Because PTH stimulates the key calcium-regulating enzyme, 1α-hydroxylase, 77 care must be taken when administered to sarcoidosis patients. There is a small case series of sarcoidosis patients treated with teriparatide for severe osteoporosis.…”
Section: Treatment Of Bone Thinning In Sarcoidosismentioning
confidence: 99%
“…The agent teriparatide may be an alternative treatment for steroid-induced bone thinning. 75,76 Because PTH stimulates the key calcium-regulating enzyme, 1α-hydroxylase, 77 care must be taken when administered to sarcoidosis patients. There is a small case series of sarcoidosis patients treated with teriparatide for severe osteoporosis.…”
Section: Treatment Of Bone Thinning In Sarcoidosismentioning
confidence: 99%
“…After 18 months, patients treated with TPTD showed a greater increase in lumbar spine and femoral neck BMD compared to risedronate. Meta‐analysis comparing TPTD and bisphosphonates has shown that TPTD increased the BMD of the lumbar spine, femoral neck and total hip to a greater extent than bisphosphonates . However, no difference in risk of non‐vertebral fractures (and adverse events) was found .…”
Section: Teriparatidementioning
confidence: 99%
“…TP is a recombinant form of human parathyroid hormone and is the first osteogenic agent to enter clinical use. Improvements in lumbar bone mineral density (BMD) of 4.54-7.48% have been reported for BP, whereas 6.4% improvement of BMD was reported after 2 years of administration of TP [9]. However, because TP is expensive and the allowed duration of administration is limited, the use of TP is problematic in terms of timing [10].…”
Section: Introductionmentioning
confidence: 99%